PHARMACISTS’ DISTRIBUTION IN NIGERIA; IMPLICATION IN THE PROVISION OF SAFE MEDICINES AND PHARMACEUTICAL CARE - Oseni, Yejide Olukemi (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The study appraised the distribution of pharmacists in the six (6) zones of Nigeria; determined the number of community pharmacies per population in each zone and in selected States; and assessed the implication of pharmacists' distribution in the provision of safe medicines and pharmaceutical care. Methods: Register of pharmacists and pharmacies for 2013 and population estimate of 2013 were used to determine the percentage of pharmacists and number of community pharmacies per population in each zone. Interviews conducted for pharmacists were analyzed. Results: About fifty-six percent (56.2%) of all registered pharmacists works in the community pharmacies. Distribution of community pharmacists shows Southwest (SW) 41.7%, Northcentral (NC) 20.6%, Southsouth (SS) 15.5%, Southeast (SE) 12.9%, Northwest (NW) 6.7% and Northeast (NE) 2.5%. In SW zone where pharmacists are highly concentrated, rural/urban distribution of community pharmacies revealed urban 89.9% and rural 10.1%, and a community pharmacy serviced 36,836 of the population. Inequitable distribution is due to low turn-out of graduate pharmacists, dearth of pharmacists abroad, poor remuneration, poor political will to employ pharmacists at the PHC level and poor amenities in the rural areas. This has led to the irrational use of medicines, non-professionals in practice, chaotic drug distribution system, poor access to safe medicines and negative effects on health indicators. Conclusion: Improvement in the country economy, increasing number of faculties of pharmacy and improved facilities in the existing ones to increase turn-out of graduate pharmacists coupled with incentives for the establishment of rural community pharmacy will increase access to safe medicines and care in Nigeria.